Generation of Aromas and Flavours 2018
DOI: 10.5772/intechopen.81168
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria Contribution to Wine Quality and Safety

Abstract: Wine production is a complex biochemical process that brings into play different microorganisms. Among these, lactic acid bacteria (LAB) play a central role in the quality of the final wine. LAB are not only responsible for the malolactic fermentation that usually occurs after the alcoholic fermentation but also contribute for other important biochemical reactions such as esterase and glycosidase activities and citric acid and methionine metabolism. Nonetheless, LAB may also contribute negatively to wine quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…Our study showed that Lactobacillus was more abundant in later stages of fermentation (after S5) which could be due to higher tolerance to alcohol concentrations ( Gold et al, 1992 ). This genus is one of the most relevant LAB in winemaking known for the production of volatile compounds that influence wine sensory attributes such as 2,3-Butanedione (Diacetyl) with a buttery, creamy aroma, geranium-smelling 2-Ethoxy-3,5-hexadiene, and vinegar-smelling acetic acid ( Inês and Falco, 2018 ). On the contrary, AAB are commonly considered to be wine spoilage bacteria due to the production of acetaldehyde and acetic acid ( Mamlouk and Gullo, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that Lactobacillus was more abundant in later stages of fermentation (after S5) which could be due to higher tolerance to alcohol concentrations ( Gold et al, 1992 ). This genus is one of the most relevant LAB in winemaking known for the production of volatile compounds that influence wine sensory attributes such as 2,3-Butanedione (Diacetyl) with a buttery, creamy aroma, geranium-smelling 2-Ethoxy-3,5-hexadiene, and vinegar-smelling acetic acid ( Inês and Falco, 2018 ). On the contrary, AAB are commonly considered to be wine spoilage bacteria due to the production of acetaldehyde and acetic acid ( Mamlouk and Gullo, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, co-inoculation of Pichia kluyveri with Saccharomyces cerevisiae can enhance 3-mercaptohexyl acetate concentration responsible for passion/grape fruit aromas in Sauvignon Blanc wines ( Carrau et al, 2020 ). Additionally, lactic acid bacteria (LAB) such as Lactobacillus and Pediococcus play important roles in citric acid metabolism and the synthesis of esters such as diethyl succinate esters (fruity aroma) impacting final wine flavor ( Inês and Falco, 2018 ). Terroir is a well-known concept to winemakers.…”
Section: Introductionmentioning
confidence: 99%
“…In wine, LAB performs a second fermentation consisting of decarboxylation of L-malic acid to L-lactic acid, designated by malolactic fermentation (MLF). In a recent review work, Inês and Falco [90] collected a panoply of bibliographic references that bring together until the date, the different described species, responsible for MLF.…”
Section: Malolactic Bacteria As a Source Of Lab Probioticsmentioning
confidence: 99%
“…The LABs are able to convert pulp substrate into ethanol, lactic acid, and acetic acid (Anal 2019). Ethanol and organic acids contribute to developing specific taste and flavor attributes (Chiang and Ismail 2006;Ayad et al 2001;Ines and Falco 2019).…”
Section: Chemical Analysismentioning
confidence: 99%